Response of eolian ecosystems to minor climatic changes - Marcomini, S. C. (2006)
The coastal dunefield of northern Buenos Aires province has been affected by two main factors: rainfall changes and urbanization. It was determine a trend to humid conditions since 1960. The changes detected on the dunefield described were: (1) increase on the vegetation cover and deflation processes over active landforms; (2) decrease in dune migration rates; (3) increase on the beach erosion; (4) degradation of the dune landforms. After one of the largest flood occurred in July 2001 in the eastern Buenos Aires, the intertidal lows of the active dunes began to be permanent flooded by an increase of the water table forming several shallow lakes. This fact induced changes on the dune ecosystem to adapt to new conditions. The lakes began to be colonized by algae and fungi probably transported by winds. Diatoms (Rhopalodia, Nitschia, Navicula, Cymbella and Neidium spp); chlorophytes (Chlamydomonas, Cosmarium, Bulbochaete, Oedogonium and Chaetosferidium spp); euglenophytes (Euglena spp). Cyanobacteria (Nostoc spp) and unidentified filamentous fungi grew between submerged macrophytes. In the bottom of the lakes appeared diatoms (Cymbella, Rhopalodia, Surirella, Amphora and Nitzschia spp.), dinofagellates and ostracods. On the lakes margins some species of vascular plants Spartina ciliata, Convolvulaceae (Dichondra sp, Panicum racemosum colonized the margins while the lakes got dry. An important bioturbation was also detected on the margins, caused by toads and worms that produced holes and tubes with complex trellis patterns, respectively.